Peran Budaya Organisasi Terhadap Kinerja Karyawan: ( Survei Pada Perusahaan Zena Purwa Perkasa ) - Tardin Tardin; Abdul Rahman Abdul Rahman (LPPM Swadaya Institute of Business and Communication, 2023)
This study aims to determine whether there is a significant influence of organizational culture and employee performance on the company Zena Purwa Perkasa Bekasi, Indonesia. The research uses quantitative and qualitative correlation description methods. The researcher uses a saturated sampling, namely all 35 staff employees of Zena Purwa Perkasa Company as the object of research. The data analysis technique in this study uses multiple linear regression analysis technique using SPSS 19. The results of the study show that organizational culture has an influence on employee performance, as indicated by the t-test value of 6.954 which is greater than the t-table value of 1.998 with a significance level of 5%. The t-test value is greater than the t-table value (6.954 > 1.998), thus organizational culture has a significant influence on employee performance.Furthermore, the determination test shows that the value of (adjusted R Square) is 0.661, which shows that work ethic and organizational culture have a 66.1% influence on employee performance, and the remaining 33.9% is influenced by other variables that are not studied. This means that the work ethic that is applied at PT. Zena Purwa Perkasa and the organizational culture that employees have can improve employee performance